The CLP and PREP protease systems coordinate maturation and degradation of the chloroplast proteome in Arabidopsis thaliana. Issue 4 (9th September 2022) - Rowland, Elden; Kim, Jitae; Friso, Giulia; Poliakov, Anton; Ponnala, Lalit; Sun, Qi; van Wijk, Klaas J.
Summary: A network of peptidases governs proteostasis in plant chloroplasts and mitochondria. This study reveals strong genetic and functional interactions in Arabidopsis between the chloroplast stromal CLP chaperone‐protease system and the PREP1, 2 peptidases, which are dually localized to chloroplast stroma and the mitochondrial matrix. Higher order mutants defective in CLP or PREP proteins were generated and analyzed by quantitative proteomics and N‐terminal proteomics (terminal amine isotopic labeling of substrates (TAILS)). Strong synergistic interactions were observed between the CLP protease system ( clpr1‐2, clpr2‐1, clpc1‐1, clpt1, clpt2) and both PREP homologs ( prep1, prep2 ) resulting in embryo lethality or growth and developmental phenotypes. Synergistic interactions were observed even when only one of the PREP proteins was lacking, suggesting that PREP1 and PREP2 have divergent substrates. Proteome phenotypes were driven by the loss of CLP protease capacity, with little impact from the PREP peptidases. Chloroplast N‐terminal proteomes s howed that many nuclear encoded chloroplast proteins have alternatively processed N‐termini in prep1prep2, clpt1clpt2 and prep1prep2clpt1clpt2 . Loss of chloroplast protease capacity interferes with stromal processing peptidase (SPP) activity due to folding stress and low levels of accumulated cleaved cTP fragments. PREP1, 2 proteolysis of cleaved cTPs is complemented by unknown proteases. A model for CLP and PREP activity within a hierarchical chloroplast proteolysis network is proposed.